Murder at Myall Creek : the trial that defined a nation - Tedeschi, Mark, 1952- (Sydney, NSW : Simon & Schuster Australia, 2016)
"One of the most shocking murder trials in Australia's legal history, and the tribulations of the man who conducted it. In 1838, eleven convicts and former convicts were put on trial for the brutal murder of 28 Aboriginal men, women and children at Myall Creek in New South Wales. The trial created an enormous amount of controversy because it was almost unknown for Europeans to be charged with the murder of Aborigines. It would become the most serious trial of mass murder in Australia’s history. The trial’s prosecutor was the Attorney General of New South Wales, John Hubert Plunkett. It proved to be Plunkett’s greatest test, as it pitted his forensic brilliance and his belief in equality before the law against the combined forces of the free settlers, the squatters, the military, the emancipists, the newspapers, and even the convict population. From the bestselling author of Kidnapped and Eugenia, Murder at Myall Creek follows the journey of the man who who arguably achieved more for modern-day civil rights in Australia than anyone else before or since"--Back cover.
Contains biographical information.
Includes bibliographical references (pages 314-318).
Keywords: Plunkett, John Hubert, -- 1802-1869.; Fleming, John Henry; Myall Creek Massacre, 1838.; Trials -- New South Wales -- Myall Creek; Aboriginal Australians -- Crimes against -- New South Wales -- Myall Creek; Massacres -- New South Wales -- Myall Creek; Aboriginal Australians -- New South Wales -- Myall Creek -- History -- 19th century; Law enforcement - Criminal law and procedure - Trials; Race relations - Violent - Massacres, murders, poisonings etc. - To 1900.; Occupations - Legal practitioners - Barristers; Animals - Livestock - Stealing and killing; Wiriyaraay people (D28) (NSW SH56-05); Law enforcement - Criminal law and procedure - Interrogation and evidence; Myall Creek (N.S.W.) -- History -- 19th century; Australia -- Law and legislation -- History -- 19th century; Australia -- History -- 19th century; Myall Creek (N NSW SH56-05); Australian